GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 24 May 2019, 08:08

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

M01-36

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 55271
M01-36  [#permalink]

Show Tags

New post 16 Sep 2014, 00:16
27
00:00
A
B
C
D
E

Difficulty:

  65% (hard)

Question Stats:

46% (01:23) correct 54% (01:14) wrong based on 228 sessions

HideShow timer Statistics

Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 55271
Re M01-36  [#permalink]

Show Tags

New post 16 Sep 2014, 00:16
1
1
Official Solution:


Question: is \(ab=1\)?

(1) \(a^2b=a\)

\(a^2b-a=0\);

\(a(ab-1)=0\): either \(a=0\) (and \(b=\text{any value}\), including zero) so in this case \(ab=0\neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(2) \(ab^2=b\)

\(ab^2-b=0\);

\(b(ab-1)=0\): either \(b=0\) (and \(a=\text{any value}\), including zero) so in this case \(ab=0 \neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(1)+(2) either \(a=b=0\), so in this case \(ab=0 \neq 1\) and the answer to the question is NO, OR \(ab=1\) and the answer to the question is YES. Two different answers, not sufficient.


Answer: E
_________________
Board of Directors
User avatar
P
Joined: 17 Jul 2014
Posts: 2551
Location: United States (IL)
Concentration: Finance, Economics
GMAT 1: 650 Q49 V30
GPA: 3.92
WE: General Management (Transportation)
GMAT ToolKit User Reviews Badge
Re: M01-36  [#permalink]

Show Tags

New post 20 Nov 2014, 20:46
why can't we conclude that:
a^2*b=a=>b=1/a
in this case a*1/a = 1
and statement 1 and 2 are both sufficient
hm..
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 55271
Re: M01-36  [#permalink]

Show Tags

New post 21 Nov 2014, 04:56
Manager
Manager
avatar
Joined: 06 Jun 2013
Posts: 106
Concentration: Technology, General Management
GMAT 1: 680 Q48 V35
GPA: 3.47
GMAT ToolKit User Reviews Badge
Re: M01-36  [#permalink]

Show Tags

New post 19 Jun 2015, 07:45
1
Hi Bunuel,

I have a question based on the solution that you have mentioned below:

Let's say a question in DS is as follows?

If x is a positive integer, is x=4?

Stmt -1) X is a root of the quadratic equation - x^2 - 12x+12=0

Stmt -2) X is a root of the quadratic equation - x^2 - 9x+20=0


Now solving each statement alone,

Stmt 1 -> Allows x value to be either x= 3,4
Stmt 2 -> Allows x value to be either x= 4,5

Now for such a Data sufficiency question, don't we find that x=4 is a common solution in both statements together and hence mark the answer as Answer choice (C) - Both statements together are sufficient but neither alone.

Now based on this understanding, for the current question,

Both statement (1) and statement (2) when taken together show that ab = 1.
Can we not select option choice (c), based on this?

Please correct me if my understanding is wrong some where?

Vijay

Bunuel wrote:
Official Solution:


Question: is \(ab=1\)?

(1) \(a^2b=a\)

\(a^2b-a=0\);

\(a(ab-1)=0\): either \(a=0\) (and \(b=\text{any value}\), including zero) so in this case \(ab=0\neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(2) \(ab^2=b\)

\(ab^2-b=0\);

\(b(ab-1)=0\): either \(b=0\) (and \(a=\text{any value}\), including zero) so in this case \(ab=0 \neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(1)+(2) either \(a=b=0\), so in this case \(ab=0 \neq 1\) and the answer to the question is NO, OR \(ab=1\) and the answer to the question is YES. Two different answers, not sufficient.


Answer: E
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 55271
Re: M01-36  [#permalink]

Show Tags

New post 19 Jun 2015, 07:55
4
svijayaug12 wrote:
Hi Bunuel,

I have a question based on the solution that you have mentioned below:

Let's say a question in DS is as follows?

If x is a positive integer, is x=4?

Stmt -1) X is a root of the quadratic equation - x^2 - 12x+12=0

Stmt -2) X is a root of the quadratic equation - x^2 - 9x+20=0


Now solving each statement alone,

Stmt 1 -> Allows x value to be either x= 3,4
Stmt 2 -> Allows x value to be either x= 4,5

Now for such a Data sufficiency question, don't we find that x=4 is a common solution in both statements together and hence mark the answer as Answer choice (C) - Both statements together are sufficient but neither alone.

Now based on this understanding, for the current question,

Both statement (1) and statement (2) when taken together show that ab = 1.
Can we not select option choice (c), based on this?

Please correct me if my understanding is wrong some where?

Vijay

Bunuel wrote:
Official Solution:


Question: is \(ab=1\)?

(1) \(a^2b=a\)

\(a^2b-a=0\);

\(a(ab-1)=0\): either \(a=0\) (and \(b=\text{any value}\), including zero) so in this case \(ab=0\neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(2) \(ab^2=b\)

\(ab^2-b=0\);

\(b(ab-1)=0\): either \(b=0\) (and \(a=\text{any value}\), including zero) so in this case \(ab=0 \neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(1)+(2) either \(a=b=0\), so in this case \(ab=0 \neq 1\) and the answer to the question is NO, OR \(ab=1\) and the answer to the question is YES. Two different answers, not sufficient.


Answer: E


When we consider two statements together we should take the values which satisfy both statements. For this question \(ab=1\) satisfies both statement, but \(a=b=0\) also satisfies both statements. So what you call "common solution" for this question is: \(ab=1\) OR \(ab=0\neq{1}\).
_________________
Intern
Intern
avatar
B
Joined: 23 Jan 2014
Posts: 27
Schools: Sloan '19 (D)
Re: M01-36  [#permalink]

Show Tags

New post 15 Aug 2016, 21:45
Sorry Bunuel, but if b=0, it will not satisfy the statement 1, will it?

Bunuel wrote:
svijayaug12 wrote:
Hi Bunuel,

I have a question based on the solution that you have mentioned below:

Let's say a question in DS is as follows?

If x is a positive integer, is x=4?

Stmt -1) X is a root of the quadratic equation - x^2 - 12x+12=0

Stmt -2) X is a root of the quadratic equation - x^2 - 9x+20=0


Now solving each statement alone,

Stmt 1 -> Allows x value to be either x= 3,4
Stmt 2 -> Allows x value to be either x= 4,5

Now for such a Data sufficiency question, don't we find that x=4 is a common solution in both statements together and hence mark the answer as Answer choice (C) - Both statements together are sufficient but neither alone.

Now based on this understanding, for the current question,

Both statement (1) and statement (2) when taken together show that ab = 1.
Can we not select option choice (c), based on this?

Please correct me if my understanding is wrong some where?

Vijay

Bunuel wrote:
Official Solution:


Question: is \(ab=1\)?

(1) \(a^2b=a\)

\(a^2b-a=0\);

\(a(ab-1)=0\): either \(a=0\) (and \(b=\text{any value}\), including zero) so in this case \(ab=0\neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(2) \(ab^2=b\)

\(ab^2-b=0\);

\(b(ab-1)=0\): either \(b=0\) (and \(a=\text{any value}\), including zero) so in this case \(ab=0 \neq 1\) OR \(ab=1\). Two different answers, not sufficient.

(1)+(2) either \(a=b=0\), so in this case \(ab=0 \neq 1\) and the answer to the question is NO, OR \(ab=1\) and the answer to the question is YES. Two different answers, not sufficient.


Answer: E


When we consider two statements together we should take the values which satisfy both statements. For this question \(ab=1\) satisfies both statement, but \(a=b=0\) also satisfies both statements. So what you call "common solution" for this question is: \(ab=1\) OR \(ab=0\neq{1}\).
Current Student
avatar
G
Joined: 03 Aug 2016
Posts: 353
Location: Canada
GMAT 1: 660 Q44 V38
GMAT 2: 690 Q46 V40
GPA: 3.9
WE: Information Technology (Consumer Products)
Re: M01-36  [#permalink]

Show Tags

New post 05 Sep 2017, 19:42
I am confused,

Why cant we say
a*b*a = a
a*b = a/a
a*b = 1

What am i missing Bunuel
_________________
My MBA Journey - https://smalldoubledouble.com
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 55271
Re: M01-36  [#permalink]

Show Tags

New post 05 Sep 2017, 20:40
mbsingh wrote:
I am confused,

Why cant we say
a*b*a = a
a*b = a/a
a*b = 1

What am i missing Bunuel


You cannot reduce a*b*a = a by a, because a can be 0, and we cannot divide by 0. By doing so you are loosing a root, namely a = 0.

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We cannot divide by zero.
_________________
Current Student
avatar
G
Joined: 03 Aug 2016
Posts: 353
Location: Canada
GMAT 1: 660 Q44 V38
GMAT 2: 690 Q46 V40
GPA: 3.9
WE: Information Technology (Consumer Products)
Re: M01-36  [#permalink]

Show Tags

New post 05 Sep 2017, 20:42
Bunuel wrote:
mbsingh wrote:
I am confused,

Why cant we say
a*b*a = a
a*b = a/a
a*b = 1

What am i missing Bunuel


You cannot reduce a*b*a = a by a, because a can be 0, and we cannot divide by 0. By doing so you are loosing a root, namely a = 0.

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We cannot divide by zero.


Interesting , didnt think of that. Thanks Bunuel
_________________
My MBA Journey - https://smalldoubledouble.com
Director
Director
User avatar
V
Joined: 12 Feb 2015
Posts: 840
Premium Member
Re: M01-36  [#permalink]

Show Tags

New post 06 Jul 2018, 10:18
We have seen numerous DS questions where statement (1) gives two values of x and statement (2) gives another two values but when only one of the values is common in the solutions from both the statements then we conclude with option "C" that is "both statements taken together are sufficient to answer the question, but neither statement alone is sufficient" because we get one definite value (which is common) of x from both the statements.

Say for example if we have a question like:-
What is the value of x?
1) x^2 = x (we find that x could be 0 or 1 therefore not sufficient)
2) (x-1)(x-2) = 0 ( we find that x could be 1 or 2)

Now answer me what would be the answer of this question, will it be "option C" that x = 1, i.e. common solution; or
"Option E" that x could either be 0 or 2 and x could be 1. Clearly when x will be 0 or 2 then it cannot be 1 and vice versa because x can assume only one value at a given point of time.

Applying the same logic for this question I am unable to understand the logic why "E" is the right answer? ab = 1 is common to both the statements.

Peripheral issue is: - by definition if a & b can assume only one value, i.e. that is "zero" then no matter what you do, you cannot have a solution of ab = 1 which is a contradiction in the question & statements itself?
_________________
"Please hit :thumbup: +1 Kudos if you like this post" :student_man:

_________________
Manish :geek:

"Only I can change my life. No one can do it for me"
Manager
Manager
User avatar
G
Joined: 20 Apr 2018
Posts: 173
Concentration: Technology, Nonprofit
WE: Analyst (Non-Profit and Government)
M01-36  [#permalink]

Show Tags

New post 21 Jul 2018, 08:43
Bunuel or chetan2u, I was able to establish the equations from statements 1 and 2.
1) a = 0 or ab = 1 (not suff.)
2) b = 0 or ab = 1 (not suff.)

I couldn't understand how to synthesize these equations together. I guess this is a very fundamental doubt. That is when we move to combine these equations, how exactly do we do it?
I combined these equations and thought ab = 1 is the only COMMON solution, hence C is the answer. Can you help me with this?
Math Expert
User avatar
V
Joined: 02 Aug 2009
Posts: 7686
Re: M01-36  [#permalink]

Show Tags

New post 21 Jul 2018, 08:54
sandman13 wrote:
Bunuel or chetan2u, I was able to establish the equations from statements 1 and 2.
1) a = 0 or ab = 1 (not suff.)
2) b = 0 or ab = 1 (not suff.)

I couldn't understand how to synthesize these equations together. I guess this is a very fundamental doubt. That is when we move to combine these equations, how exactly do we do it?
I combined these equations and thought ab = 1 is the only COMMON solution, hence C is the answer. Can you help me with this?



Hi...
If the two statements had given two different values of a,
I) say a=0 or ab=1
2) say a=2 or ab=1
Them a cannot be both values and hence only possibility is ab=1

But here we have two solutions..
1) ab=1
Or
2) a=b=0

Both the above will satisfy the equation..
So ab=0 or ab=1
_________________
Manager
Manager
User avatar
G
Joined: 20 Apr 2018
Posts: 173
Concentration: Technology, Nonprofit
WE: Analyst (Non-Profit and Government)
M01-36  [#permalink]

Show Tags

New post 21 Jul 2018, 09:58
chetan2u wrote:
Hi...
If the two statements had given two different values of a,
I) say a=0 or ab=1
2) say a=2 or ab=1
Them a cannot be both values and hence only possibility is ab=1

But here we have two solutions..
1) ab=1
Or
2) a=b=0

Both the above will satisfy the equation..
So ab=0 or ab=1


Hi chetan2u, thanks for the prompt reply.
Just a clarification: why did you pick that COMBINATION of possible solutions?
Let me make this a bit abstract.
Say,
S1: X or Y
(where X and Y are some sets of solution(s))
S2: Z or Y

Now, combining the two: (X or Y) and (Z or Y) ... is what? I think I studied this back in school, but I have no clear recollection of how those compliments and unions work.
I was able to DRAW the event (X or Y) and (Z or Y) on a Venn diagram and get the result Y or (X and Z)

In our problem, this would basically translate as follows:

S1: a = 0 OR ab = 1
S2: b = 0 OR ab = 1

Combining, we get EITHER
1. ab = 1
OR
2. a = 0 AND b = 0

But this seems like a REALLY long way to solve the problem. What am I missing?
>> !!!

You do not have the required permissions to view the files attached to this post.

Intern
Intern
avatar
B
Joined: 16 Apr 2014
Posts: 16
Re: M01-36  [#permalink]

Show Tags

New post 16 Dec 2018, 03:53
Bunuel

"Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We cannot divide by zero."

If its given in problem a & b are not zero, then answer will be D. Right?

Pl. clarify!
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 55271
Re: M01-36  [#permalink]

Show Tags

New post 16 Dec 2018, 07:42
16SK16 wrote:
Bunuel

"Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We cannot divide by zero."

If its given in problem a & b are not zero, then answer will be D. Right?

Pl. clarify!


Right. In this case we could reduce (1) by a and get ab = 1 and reduce (2) by b and get ab = 1.
_________________
Manager
Manager
avatar
G
Joined: 22 Jun 2017
Posts: 178
Location: Argentina
Schools: HBS, Stanford, Wharton
GMAT 1: 630 Q43 V34
Premium Member Reviews Badge
Re M01-36  [#permalink]

Show Tags

New post 18 Feb 2019, 13:23
I think this is a high-quality question and I agree with explanation.
_________________
The HARDER you work, the LUCKIER you get.
Intern
Intern
avatar
B
Joined: 19 Feb 2019
Posts: 5
Premium Member CAT Tests
Re: M01-36  [#permalink]

Show Tags

New post 21 Mar 2019, 20:04
sandman13 wrote:
I was able to establish the equations from statements 1 and 2.
1) a = 0 or ab = 1 (not suff.)
2) b = 0 or ab = 1 (not suff.)

I couldn't understand how to synthesize these equations together. I guess this is a very fundamental doubt. That is when we move to combine these equations, how exactly do we do it?
I combined these equations and thought ab = 1 is the only COMMON solution, hence C is the answer. Can you help me with this?


Very interesting question. I had the same problem but I guess this is how the solution was arrived at;

1) a = 0 or ab = 1 (not suff.) => the fact that a = 0 also implies that ab = 0
2) b = 0 or ab = 1 (not suff.) => the fact that b = 0 also implies that ab = 0

so combining (1) and (2), we still have ab = 0 or ab = 1. Not Sufficient
GMAT Club Bot
Re: M01-36   [#permalink] 21 Mar 2019, 20:04
Display posts from previous: Sort by

M01-36

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  

Moderators: chetan2u, Bunuel



Copyright

GMAT Club MBA Forum Home| About| Terms and Conditions and Privacy Policy| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.